Perbedaan Hematokrit Darah Segar dan Darah Simpan (30 Hari) DI UTD RSAM Bandar Lampung - Syuhada Syuhada; Aditya Aditya; Ira Candrawijaya (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: at the time of erythrocyte blood collection will be damaged, every day the viability of erythrocytes continues to decrease due to decreased levels of ATP (Adenosine Triphosphate), so that if ATP levels decrease then the loss of membrane lipids, membrane stiffens and the shape of the discs into spherical (discs) not central polar and small size). This study aimed to determine the difference in the hematocrit value of fresh blood with blood storage (30 days) at UTD Dr. H. Abdul Moeloek Lampung in 2020. Method: The type of research used in this study is quantitative observational with non-probability sampling design. The sample used in this study was respondents who were willing to donate their blood at UTD RSUD Dr. H. Abdul Moeloek Lampung. Analysis of data using the Wilcoxon formula. Results: obtained p value> 0.05 which means there is no significant difference between fresh blood and blood storage (30 days) at UTD Dr. H. Abdul Moeloek Lampung. Conclusion: donor blood management and donor blood quality at the site are in good condition so that donor blood can be given to recipients, without having significant component changes